2022
DOI: 10.1007/s11133-022-09517-3
|View full text |Cite
|
Sign up to set email alerts
|

Code Ethnography and the Materiality of Power in Internet Governance

Abstract: The purpose of this article is to discuss an ethnography of code, specifically code ethnography, a method for examining code as a socio-technical actor, considering its social, political, and economic dynamics in the context of digital infrastructures. While it can be applied to any code, the article presents the results of code ethnography application in the study of internet interconnection dynamics, having the Border Gateway Protocol (BGP) as code and two of the largest internet exchange points (IXPs) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
3
0
1
Order By: Relevance
“…For this research, we engaged in code ethnography (Rosa, 2022) of GSM, internet and 5G technologies, as well as participant observation in the main standard-development organisations of the internet and 5G. Our methodological assumptiontaken from world system theory (Wallerstein, 2004) is that the character and content of imaginaries and their underpinning ideologies creatively reflect the position of actors in the global division of labour.…”
Section: Ideologies and Materialitiesmentioning
confidence: 99%
“…For this research, we engaged in code ethnography (Rosa, 2022) of GSM, internet and 5G technologies, as well as participant observation in the main standard-development organisations of the internet and 5G. Our methodological assumptiontaken from world system theory (Wallerstein, 2004) is that the character and content of imaginaries and their underpinning ideologies creatively reflect the position of actors in the global division of labour.…”
Section: Ideologies and Materialitiesmentioning
confidence: 99%
“…Database ethnographies aim at complementing the collection and categorization of data with qualitative context (Schuurman, 2008), enhancing data interpretation (Zhang et al, 2018) and analyzing the resulting datasets as fieldsites (Burns & Wark, 2020), but ethnographic approaches can also contribute to structuring statistical inquiry (Ford, 2014), narrating quantitative data qualitatively (Dourish & Gómez Cruz, 2018) and establishing ground truths for big data analyses (Bjerre-Nielsen & Glavind, 2022). Ethnographers working with modeling experts have demonstrated that the complexity of machine learning models escapes their users (Kolkman, 2022), and the ones examining code have evidenced its key role as a socio-technical actor (Rosa, 2022).…”
Section: Ethnography Of the Digital Algorithmic Automatedmentioning
confidence: 99%
“…I have argued that ethnographers can treat open science calls and practices not just as chances to prove that we are not lying, but as provocations to treat facticity as an object of our study, and we can treat the sharing of research materials as not only a strategy to adopt, but a knowledge practice to study. Indeed, the profusion of available data, instruments, research designs, code, and more across differing platforms and audiences that has resulted from open science policies and practices offers itself for ethnographic analysis, including "code ethnography" (Rosa, 2022), policy ethnography, ethnography of documentation, and ethnography of infrastructure (Star, 1999): open science, in other words, may be a great gift to ethnographers of science. By treating calls and requirements for open science, data-sharing, and transparency as not just methodological, but also empirical matters, we gain new questions for analysis, new field sites, and opportunities to revisit and reexamine core questions in the ethnographic study of science.…”
Section: Data-sharing For Governance: Open Science and The Problem Of...mentioning
confidence: 99%